Contractile and Extensible Molecular Figures‐of‐Eight. Issue 41 (1st September 2015) - Niess, Frédéric; Duplan, Vincent; Diercks, Christian S.; Sauvage, Jean‐Pierre
Abstract Two large rings, 66‐ (m‐66) and 78‐membered (m‐78) rings, each one incorporating two pairs of transition‐metal‐complexing units, have been prepared. The coordinating fragments are alternating bi‐ and tridentate chelating groups, namely, 2, 9‐diphenyl‐1, 10‐phenanthroline (dpp) and 2, 2′, 2′, 6′′‐terpyridine (terpy) respectively. Both macrocycles form molecular figures‐of‐eight in the presence of FeII, affording a classical bis‐terpy complex as the central core. The larger m‐78 ring can accommodate a four‐coordinate CuI center with the formation of a {Cu(dpp)2}+ central complex and a highly twisted figure‐of‐eight backbone, whereas m‐66 is too small to coordinate CuI. Macrocycle m‐78 thus affords stable complexes with both FeII and CuI; the ligand around the metal changes from (terpy)2 to (dpp)2. This bimodal coordination situation allows for a large amplitude rearrangement of the organic backbone. When coordinated to preferentially octahedrally coordinated FeII or CuII, the height of the molecule along the coordinating axis of the tridentate terpy ligands is only about 11 Å, whereas the height of the molecule along the same vertical axis is several times as large for the tetrahedral CuI complex. Chemically or electrochemically driven contraction and extension motions along a defined axis make this figure‐of‐eight particularly promising as a new class of molecular machine prototype for use as a constitutive element in muscle‐like dynamic systems.